ATRT-23. SMARCB1-DEPENDENCIES IN ATYPICAL TERATOID/RHABDOID TUMOURS: A STRATEGY FOR PRE-CLINICAL THERAPEUTIC TARGET IDENTIFICATION IN THE ABSENCE OF ACTIONABLE MUTATIONS. Issue 2 (22nd June 2018) - Finetti, Martina Anna; Selby, Matthew p; Pons, Alicia del-Carpio; Batting, Sarah; Wood, James A; Barker, James M; Smith, Amanda; Crosier, Stephen; Bashton, Matthew; Pickles, Jessica C; Fairchild, Amy R; Avery, Aimee; et al.
Abstract: ATRTs have low mutation rates and few classically-actionable variants to direct molecularly targeted therapies; loss of SMARCB1 is the sole recurrent mutational event in >90% of ATRTs. We have designed and implemented a genome-scale strategy for target identification and prioritization in tumors devoid of significant actionable mutations. Re-expression of SMARCB1 causes ATRT cells to cease proliferation and differentiate; we therefore hypothesized that identifying and counteracting critical downstream SMARCB1-dependent events represents a primary route to therapeutic intervention. We identify such events using an integrated genome-wide approach encompassing genome-scale CRISPR/Cas9 functional screens (GeCKO screening; 122, 411 sgRNAs) alongside expression/DNA methylation profiling of primary ATRTs and ATRT cells following SMARCB1 re-expression and/or treatment with demethylating agents. Cross-referencing these analyses, we use a rational selection algorithm, to identify critical tumorigenic genes/pathways and proceed to validate their ability to be targeted as therapeutic targets. Our strategy identifies, ranks and prioritizes multiple SMARCB1-dependent pathways/genes functionally essential to ATRT, and characteristic of the primary tumour; including those previously described (Rb/CDK4/6, SHH, MYC), those less well evidenced (mTOR, TGF-β, HGF, Stat3/Jak) and novel SMARCB1-dependent synthetic lethalities (NuA4 complex, PIM1). We also describe the repressive genome-wide effect of SMARCB1 mutation on the transcriptome, through altered SWI/SNF binding, associated histone marks and localized hypermethylation and the therapeutic possibilities implied therein. Data and web-based interactive analysis and visualization tools will be made publically available to help guide and benchmark future pre-clinical testing in ATRT. This study pinpoints SMARCB1-dependent therapeutic susceptibilities in MRTs with the capacity to inform future treatment strategies.